PANDEMIC STRICKEN PREGNANCY AND IMPORTANCE OF PRENATAL ATTACHMENT; A REVIEW PAPER - Bishnu Roy, Moumita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Perceived stress and anxiety are normal psychodynamics of pregnancy which was triggered with the advent of Covid-19 pandemic. The consequences and modes of prevention from the deadly disease both were exhaustive and detrimental from a prospective view of Positive Pregnancy psychology. The paper thus highlights the role of prenatal attachment as expressed in various studies among pregnant mothers during the covid 19 pandemic and objectively focuses the findings from the papers, which included prenatal attachment or antenatal attachment or prenatal bonding. This review thus clarifies that prenatal attachment is unique attribute of parents to be which needs more acceptance and promotion. The objective of the paper thus is to highlight that promotion of prenatal attachment was so less explored during the pandemic, where its need was highest as suggestive from various studies concluded that stress, anxiety and psychological wellbeing of mothers were grossly affected during pandemic and poor prenatal attachment among mothers were reported. Needless to justify the importance of promotion of prenatal attachment. The studies reviewed, indicated that prenatal attachment or bonding needs promotion and awareness during crisis all the more for a pregnant mother for a healthy outcome of pregnancy and beyond.